Understanding Mechanisms of GLI-Mediated Transcription during Craniofacial Development and Disease Using the Ciliopathic Mutant, talpid2 - Chang, Ya-Ting; Chaturvedi, Praneet; Schock, Elizabeth N.; Brugmann, Samantha A. (Frontiers in Physiology, 2016)
The primary cilium is a ubiquitous, microtubule-based organelle that cells utilize to transduce molecular signals. Ciliopathies are a group of diseases that are caused by a disruption in the structure or function of the primary cilium. Over 30% of all ciliopathies are primarily defined by their craniofacial phenotypes, which typically include midfacial defects, cleft lip/palate, micrognathia, aglossia and craniosynostosis. The frequency and severity of craniofacial phenotypes in ciliopathies emphasizes the importance of the cilium during development of the craniofacial complex. Molecularly, many ciliopathic mutants, including the avian talpid2 (ta2), report pathologically high levels of full-length GLI3 (GLI3FL), which can go on to function as an activator (GLIA), and reduced production of truncated GLI3 (GLI3T), which can go on to function as a repressor (GLIR). These observations suggest that the craniofacial phenotypes of ciliary mutants like ta2 are caused either by excessive activity of the GLIA or reduced activity of GLIR. To decipher between these two scenarios, we examined GLI3 occupation at the regulatory regions of target genes and subsequent target gene expression. Using in silico strategies we identified consensus GLI binding regions (GBRs) in the avian genome and confirmed GLI3 binding to the regulatory regions of its targets by chromatin immunoprecipitation (ChIP). In ta2 mutants, there was a strikingly low number of GLI3 target genes that had significantly increased expression in facial prominences compared to the control embryo and GLI3 occupancy at GBRs associated with target genes was largely reduced. In vitro DNA binding assays, further supported ChIP results, indicated that the excessive GLI3FL generated in ta2 mutants did not bind to GBRs. In light of these results, we explored the possibility of GLI co-regulator proteins playing a role in regulatory mechanism of GLI-mediated transcription. Taken together our studies suggest that craniofacial ciliopathic phenotypes are produced via reduced GLIT production, allowing for target gene transcription to be mediated by the combinatorial code of GLI co-regulators.